2011
DOI: 10.1100/2011/583603
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effects of Triflusal, S-Adenosylmethionine, and Dextromethorphan over Intestinal Ischemia/Reperfusion Injury

Abstract: Ischemia/reperfusion (I/R) is a condition that stimulates an intense inflammatory response. No ideal treatment exists. Triflusal is an antiplatelet salicylate derivative with anti-inflammatory effects. S-adenosylmethionine is a metabolic precursor for glutathione, an endogenous antioxidant. Dextromethorphan is a low-affinity N-methyl-D-aspartate receptor inhibitor. There is evidence that these agents modulate some of the pathways involved in I/R physiopathology. Intestinal I/R was induced in rats by clamping t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…It is a precursor of glutathione, a major cellular antioxidant (Lu, 2000;Oz et al, 2005). SAMe has shown protection against oxidative stress in models of colitis, intestinal ischaemia, liver disorders, and even neurological disorders in humans (Lu, 2000;Oz et al, 2005;Camara-Lemarroy et al, 2011;Michael Brown et al, 2012;Au et al, 2013). In dogs, SAMe is hepatoprotective, and has been used as an alternative to N-acetylcysteine in acetaminophen toxicity (Wallace et al, 2002;Au et al, 2013).…”
Section: Treatment and Outcomementioning
confidence: 99%
“…It is a precursor of glutathione, a major cellular antioxidant (Lu, 2000;Oz et al, 2005). SAMe has shown protection against oxidative stress in models of colitis, intestinal ischaemia, liver disorders, and even neurological disorders in humans (Lu, 2000;Oz et al, 2005;Camara-Lemarroy et al, 2011;Michael Brown et al, 2012;Au et al, 2013). In dogs, SAMe is hepatoprotective, and has been used as an alternative to N-acetylcysteine in acetaminophen toxicity (Wallace et al, 2002;Au et al, 2013).…”
Section: Treatment and Outcomementioning
confidence: 99%
“…Dextromethorphan (DXM) is a CNS active agent widely used as an effective and safe cough suppressant [20]. Interestingly, several studies have revealed that DXM provides significant CNS antioxidant effects [21][22][23][24][25][26]. Various investigations have confirmed the neuroprotective properties of DXM in complications such as cerebral ischemia, Parkinson's disease, multiple sclerosis, spinal cord injury, and epilepsy [21,[27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%